PROFIL TINGKAT KEMAMPUAN DAYA TAHAN (VO2 MAX) ATLET TENIS MEJA JUNIOR PUTRA KLUB MALAY SPORT PEKANBARU - ', Dudi; ', Saripin; Agust, Kristi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of observations made by the researchers of the table tennis junior men athletes Malay Sport Club Pekanbaru, researchers found a problem that athletes often rely on during training, athletes are easily breathless during a physical tests, when the game was fierce and long, physical athletes looks decreases, when competing athletes are not optimal in return the hit of opponent when it entered into a last final, less good in the long rally game in returning the hit of opponent when the game goes longer. Because of that the purpose of this study is to determine the ability levels of (VO2Max) Endurance athletes junior men table tennis Malay Sport Club Pekanbaru. This research is a descriptive that aims to describe or depict such things as they are. The population in this study are all junior men table tennis athletes Malay Sport Club Pekanbaru amounting to 8 people. Techniques of taking sample which is used total sampling techniques, where the total population sampled. To obtain data on profile of VO2Max ability level in junior men table tennis athletes in this study used a Bleep Test. Based on the results of data analysis can be concluded that from 8 samples junior men table tennis athletes of 0% have (VO2Max) in Superior category, 25% have (VO2Max) in Excellent category, 12,5% have (VO2Max) in Good category, 25% have (VO2Max) in Fair category, 25% have (VO2Max) in Poor category, and 12,5% have (VO2Max) in category of Very Poor. So It can be concluded that the rate of (VO2Max) Junior Men Table Tennis Athletes Malay Sport Sport Pekanbaru are Fair with average of (VO2Max) ability level in junior men table tennis athletes Malay Sport Club Pekanbaru are 42,3%.Key Words: VO2Max of Endurance, Table Tennis.